The Role of Music in Everyday Life During the First Wave of the Coronavirus Pandemic: A Mixed-Methods Exploratory Study - Carlson, Emily; Wilson, Johanna; Baltazar, Margarida; Duman, Deniz; Peltola, Henna-Riikka; Toiviainen, Petri; Saarikallio, Suvi (Frontiers in Psychology, 2021)
Although music is known to be a part of everyday life and a resource for mood and emotion management, everyday life has changed significantly for many due to the global coronavirus pandemic, making the role of music in everyday life less certain. An online survey in which participants responded to Likert scale questions as well as providing free text responses was used to explore how participants were engaging with music during the first wave of the pandemic, whether and how they were using music for mood regulation, and how their engagement with music related to their experiences of worry and anxiety resulting from the pandemic. Results indicated that, for the majority of participants, while many felt their use of music had changed since the beginning of the pandemic, the amount of their music listening behaviors were either unaffected by the pandemic or increased. This was especially true of listening to self-selected music and watching live streamed concerts. Analysis revealed correlations between participants’ use of mood for music regulation, their musical engagement, and their levels of anxiety and worry. A small number of participants described having negative emotional responses to music, the majority of whom also reported severe levels of anxiety.